Systemic Response: Developing a Strategic Response to Support Young Men of Color during COVID-19 Pandemic - Eligio Martinez; Derrick R. Brooms; William Franklin; Matthew Smith; Andre Bailey; Markel Quarles (MDPI AG, 2021)
The aim of this work is to provide insight into the California State University Young Men of Color Consortium (CSU YMOC), which was created to explore the unique challenges young men of color face during their postsecondary experiences, as well as advance effective approaches to better support them. Specifically, we focus on CSU Male Success Initiative programs and detail how campus partners worked collaboratively to support men of color during the previous academic year amid the COVID-19 pandemic. Given the ways that the ongoing COVID-19 pandemic disrupted education across the P-16 spectrum, the MSIs were positioned uniquely to support some of the challenges that students endured. Recent reports reveal that the pandemic has exacerbated a number of difficulties, both old and new(er), that men of color experience in their college years, from accessing and transitioning to matriculating and persisting in higher education. We provide an overview of the CSU YMOC Consortium and present details about one program element (Critical Conversations) we incorporated this year as a measure to be responsive to challenges brought on by the pandemic. Finally, partners at three institutions share reflections on how their MSI shifted their efforts to meet students' needs and provide support.